Malnutrition and its association with functional, cognitive and psychological status among Palestinian older adults in long-term care houses - Badrasawi, Manal.; Badrasawi, Kamal J I; Irshaid, Alma; Hamdan, May (Routledge, Taylor & Francis Group, 2019)
Older adults often suffer from psychological, functional and health-related diseases. Literature has documented the relationship between, malnutrition with adverse health outcomes. This study aims to examine the relationship between malnutrition with the cognitive, functional and psychological status of older adults living in long-term care houses. The study employed a cross-sectional approach in which 99 participants were included from seven nursing homes in six different cities across the West Bank, Palestine. The nutritional status of older adults was assessed using anthropometric measurements and meal patterns. Malnutrition risk was assessed using Mini Nutritional Assessment; the cognitive function using Mini Mental Status Examination; the functional status using the Activity of Daily Living. Results: A total of 99 participants (45.5%) men and (54.5%) women were included in the final data analysis. The results revealed 47% of the participants were at risk of malnutrition, while 23% were malnourished. Variables that were significantly associated with malnutrition; male gender, higher score of depressive symptoms, and impaired cognitive function, p < .05 using chi square test. However, number of meals and hours of overnight fasting were not associated with being malnourished. Greater dependency level was associated with high risk of malnutrition, p < .05 using One Way ANOVA test.